Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Impact Report 2021-2022 - 4Korners (2022)

Rapport d'impact 2021-2022 - 4Korners (2022)

Impact Report 2020-2021 - 4Korners (2021)

Rapport d'impact 2020-2021 - 4Korners (2021)

Impact Report 2019-2020 - 4Korners (2020)

Rapport d'impact 2019-2020 - 4Korners (2020)